2017
DOI: 10.1016/j.breast.2017.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Role of total tumour load of sentinel lymph node on survival in early breast cancer patients

Abstract: SLN TTL permits the differentiation between two patient groups in terms of DFS and OS, independently of axillary staging (pN), age and tumour characteristics (size, grade, lymphovascular invasion). This new data confirms the clinical value of low axillary involvement and could partially replace the information that staging of the entire axilla provides in patients on whom no axillary lymph node dissection is performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 40 publications
2
45
1
Order By: Relevance
“…In our study, TTL had the best AUROC for both the all patients group and macrometastatic group suggesting greater accuracy than the other two methods used. Peg et al have shown that TTL correlates with disease‐free survival, local recurrence disease‐free survival, and overall survival using their cutoff of 25 000 copies 10 . They suggest that OSNA assessment could partially replace the staging information that ALND provides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, TTL had the best AUROC for both the all patients group and macrometastatic group suggesting greater accuracy than the other two methods used. Peg et al have shown that TTL correlates with disease‐free survival, local recurrence disease‐free survival, and overall survival using their cutoff of 25 000 copies 10 . They suggest that OSNA assessment could partially replace the staging information that ALND provides.…”
Section: Discussionmentioning
confidence: 99%
“…Given this, OSNA can be predictive of four node involvement with a copy number of >100 000 copies/µL 7 and total tumor load (TTL—total of copy numbers in submitted nodes) can be used to differentiate patients using Z0011 criteria 8 . TTL has proven a focus of research with multiple studies showing it to be an independent predictor of higher nodal involvement 9‐12 …”
Section: Introductionmentioning
confidence: 99%
“…The number of ALND procedures has decreased drastically after publication of the ACOSOG Z0011 study showing that ALND provided no benefit in terms of disease‐free survival or overall survival in a subgroup of patients with one or two positive SLNs . It was speculated that the information of the number of involved LNs provided by the ALND may be replaced by the extensive investigation of the detected SLN . We have reported previously that CK19 mRNA copy number detected by the OSNA assay using a whole‐SLN analysis could become a valuable method for predicting non‐SLN and the presence of ≥4 LN metastases .…”
Section: Discussionmentioning
confidence: 99%
“…19 It was speculated that the information of the number of involved LNs provided by the ALND may be replaced by the extensive investigation of the detected SLN. 20 We have reported previously that CK19 mRNA copy number detected by the OSNA assay using a whole-SLN analysis could become a valuable method for predicting non-SLN and the presence of ≥4 LN metastases. 9 However, Ogiya et al reported that the non-SLN metastasis positivity rate was the same in cases with SLN micrometastases and those with SLN macrometastases.…”
Section: Discussionmentioning
confidence: 99%
“…The TTL score was proved to be an independent predictor factor of the axillary nodal status, where only 14.7% of patients with TTL beneath 15.000 copies/µl had other positive non-SLN [21]. Recently, the PLUTTO study results also proved its impact on the prognosis of BC patients [22]. Therefore, the OPTIMAL study (OPTimizing Irradiation through Molecular Assessment of Lymph node) aims to demonstrate the non-inferiority of incidental irradiation of axillary nodes in comparison to intentional irradiation in terms of the 5-year DFS of patients with early-stage BC and limited involvement of the SLN according to the OSNA quantitative score.…”
Section: Introductionmentioning
confidence: 98%